2021
DOI: 10.1002/aws2.1246
|View full text |Cite
|
Sign up to set email alerts
|

Lead pipe andlead–tinsolder scale formation and structure: A conceptual model

Abstract: Lead-tin solder and lead service lines (LSLs) are important sources of lead, and after LSLs are removed, lead-tin solder will remain a major source of lead.A better understanding of the factors that control lead release from solder joints can help water utilities reduce lead. This paper reviews the reactions that take place at galvanic connections involving both lead-tin solder and lead pipe in contact with copper. A conceptual model based on these reactions was developed and is presented here to explain how s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Specifically, the mean lead concentrations dropped by 45% and 60% in Marston and Moffat pH 8.8 loops, respectively, compared to the pre‐treatment conditions ( p < .0001). The decrease in lead levels for the high pH treatment can be attributed to the lower solubility of the lead carbonate species at high pH, as discussed by Schock et al (1996) or a change in scale structure, such as decreased scale porosity (Snoeyink et al, 2021).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Specifically, the mean lead concentrations dropped by 45% and 60% in Marston and Moffat pH 8.8 loops, respectively, compared to the pre‐treatment conditions ( p < .0001). The decrease in lead levels for the high pH treatment can be attributed to the lower solubility of the lead carbonate species at high pH, as discussed by Schock et al (1996) or a change in scale structure, such as decreased scale porosity (Snoeyink et al, 2021).…”
Section: Resultsmentioning
confidence: 96%
“…One of the LSLs on each rack was segmented to allow portions of the LSL to be removed and destructively analyzed for elemental and scale composition. Results from the pipe scale analysis have been reported by Snoeyink et al (2021) but are discussed in more detail in this study. Additional details about the scale analysis methods and results can be found in Appendix S1.…”
Section: Pipe Rack Setup and Operationmentioning
confidence: 91%
“…By comparison, PFAS are present at concentration orders of magnitude lower than IAs and are much more selective (e.g., K PFOA/C = 10 4. 36 ), 39 so it is expected that PFAS of interest (such as PFOA) will break through much later than IAs. In fact, studies have reported a breakthrough in the 10 6 BVs range for PFOA in groundwater on PFA694E.…”
Section: Batch Competitive Isotherm Experiment a Competitive Ie (Ie-a...mentioning
confidence: 99%
“…Changes in source water quality brought about gradually (e.g., seasonal changes) or rapidly (e.g., alternating source inputs) could likewise lead to temporal effluent water quality changes. Water quality shifts may impact the distribution system where (i) stable alkalinity and pH are typically desired and (ii) chloride, sulfate, and bicarbonate concentrations affect corrosion potential as indicated by the Larson ratio (LR) for iron-based pipes (e.g., LR >0.8 is shown to increase iron release) and the chloride-to-sulfate mass ratio (CSMR) for galvanic corrosion (e.g., CSMR >0.5 is shown to increase lead release). ,− Therefore, it is important to understand transient water quality to minimize potential unintended consequences when implementing SB-AEX for PFAS removal, and the development of an ion exchange column model (IEX-CM) to simulate effluent IA and PFAS concentrations would be beneficial.…”
Section: Introductionmentioning
confidence: 99%
“…The main lead source in a lead pipe is the pipe itself. Besides lead-manufactured pipes, another source of lead in non-lead pipe systems are brass fixtures and lead-solder connections [41][42][43][44][45]. These fittings represent discrete sources of lead that may give rise to significant lead concentrations in drinking water.…”
Section: Materials Used To Manufacture Drinking Water Distribution Pi...mentioning
confidence: 99%